Thanking strategies in the filmfare and academy award acceptance speeches / Savithiammal David - Savithiammal , David (2020)
The present research endeavours to shed light on the thanking strategies that are used by the recipients of the Filmfare Awards and the Academy Awards in their acceptance speeches. Award acceptance speeches are direct expressions of gratitude. However, to date no research has been done on it. Therefore it is imperative to investigate the thanking strategies employed in these acceptance speeches in an attempt to close the gap in this field. To understand and define the thanking strategies, various models and theories of thanking are explored, which in turn shed light on several important concepts. The characteristics of the thanking is that it is an expressive speech which functions as a tool to express gratitude towards a beneficial act by a third party. In an attempt to identify various thanking strategies, the current research delves into literature that investigates various thanking strategies and their realizations. Using a quantitative and qualitative approach this study attempts to obtain a clear insight into the thanking strategies used by the recipients of the six main categories of the Filmfare and Academy Awards in their acceptance speech. The acceptance speeches are coded based on the thanking strategies put forward by Aijmer (1996). The findings of this study demonstrate that the recipients of the Academy Awards uses more thanking strategies than the recipients of the Filmfare Awards. The findings reveal that the most used thanking strategy is thanking somebody explicitly while the least used thanking strategy is commenting on one’s own role by suppressing one’s own importance. The results also identify the formulaic expression ‘thank’ and the base of the realization of thanking. The research proposes recommendations on how Aijmer’s (1996) thanking strategies can be incorporated in the readers’ speeches when expressing gratitude which is difficult even for native speakers.